MITIGASI BENCANA BERBASIS KEARIFAN LOKAL MASYARAKAT DALAM MENGURANGI DAMPAK RISIKO BENCANA GEMPA BUMI DAN TSUNAMI DI KECAMATAN PAGAI UTARA KEPULAUAN MENTAWAI - Hilky Marbun, Rosna; Juita, Erna; Nefilinda, Nefilinda (Jurnal Spasial, 2025)
Indonesia is one of the countries most vulnerable to tectonic earthquakes and tsunamis, particularly in West Sumatra Province. North Pagai District in the Mentawai Islands is considered a high-risk area due to its proximity to the Mentawai Megathrust zone and active tectonic plate movements. Earthquakes and tsunamis not only cause loss of life and physical destruction but also disrupt social activities and leave long-term psychological impacts on affected communities. This study aims to examine community-based disaster mitigation through local wisdom in reducing the risks and impacts of earthquakes and tsunamis in North Pagai District, Mentawai Islands. The study employed a mixed-methods approach involving three villages with a total population of 1,094 households, from which 91 households were selected as research samples. Data were analyzed using descriptive and interactive analysis techniques. The findings reveal that, first, the impacts of earthquakes and tsunamis in North Pagai District are extensive and significant, with a “very high” impact level (75%), indicating that the consequences extend beyond material losses and require serious attention to ecological and psychological recovery. Second, the disaster has severely affected the socio-economic sector, resulting in substantial financial losses with a “high” impact level (82%). Third, local wisdom practices, including the Arat Sabulungan tradition, Uma, and Punen rituals, have proven to be highly effective in helping communities cope with the severe impacts of earthquakes and tsunamis. Fourth, the community has demonstrated strong responsiveness and adaptive capacity in dealing with earthquake and tsunami hazards. These findings highlight the important role of local wisdom as a community-based disaster mitigation strategy that strengthens resilience and supports sustainable disaster risk reduction in disaster-prone areas.